High-strength mortar adopting coal gangue fine powder and preparation method of high-strength mortar
By calcining and modifying coal gangue fine powder at high temperature, removing impurities and improving activation degree, and preparing high-strength mortar with other components, the problem of reduced strength and durability when coal gangue is incorporated into concrete is solved, and efficient resource re-realization is achieved Utilization and performance improvement.
Patent Information
- Application Number
- CN202411594445.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-09
- Publication Date
- 2025-02-18
AI Technical Summary
Coal gangue contains a large amount of useless coal and impurities, resulting in reduced strength and durability when incorporated into concrete.
By calcining and modifying coal gangue fine powder at high temperature, carbon components and impurities are removed, and their activation degree is improved. Combined with silicate cement, silica fume, water reducer, aggregate and other components, a high-strength mortar is prepared. .
It significantly improves the compressive strength and durability of concrete, reduces its dependence on natural sand and gravel resources, and is in line with the concept of environmental protection and sustainable development.
Smart Images

Figure BDA0005126441460000071 
Figure BDA0005126441460000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of coal gangue concrete, and more specifically, to a high-strength mortar using fine coal gangue powder and a preparation method thereof. Background Art
[0002] Gangue is solid waste discharged during coal mining and coal washing, mainly including tunneling gangue during tunneling, gangue mined from the roof, floor and interlayer during mining, and washed gangue picked out during coal washing. Gangue contains a large amount of useless coal, rocks, soil and other impurities. Traditionally, gangue has been regarded as a source of environmental pollution and a waste of resources, and is often disposed of by landfill or stacking. However, with the increasing attention paid to sustainable development and resource recycling, the reuse of gangue has gradually received attention.
[0003] After being crushed, cleaned and other treatments, coal gangue can be added to concrete mortar, which can not only reduce the demand for traditional stone materials, save resources, but also reduce damage to the natural environment. At the same time, through proper treatment and improvement, coal gangue can provide a certain strength and stability to meet the requirements of some construction projects. Therefore, this technology has broad application prospects in the construction industry and helps promote the goal of sustainable development.
[0004] Although coal gangue has potential in concrete applications, it contains a large amount of useless coal and impurities. When concrete is in a humid environment, the sulfide and sulfate in the impurities will gradually decompose and expand, which will affect the strength and durability of the concrete. Alkali metal ions react with silicates in concrete to form alkali silica gel, which increases the internal stress of the concrete, causing cracking and damage to the concrete, and reduces the compressive strength and durability of the concrete. Secondly, useless coal has a poor ability to participate in the hydration reaction of concrete, which leads to insufficient hydration reaction in concrete and unevenness inside the concrete, affecting the hardening process of concrete and affecting the strength and durability of concrete. Summary of the invention
[0005] In order to solve the problem that the existing coal gangue contains a lot of impurities, which leads to reduced strength and durability of concrete mixed with the coal gangue, the present application provides a high-strength mortar using fine coal gangue powder and a preparation method thereof.
[0006] In the first aspect, the present application provides a high-strength mortar using fine coal gangue powder, which adopts the following technical solution: A high-strength mortar using fine coal gangue powder, whose components, by weight, include 60-100 parts of silicate cement, 50-80 parts of calcined modified coal gangue fine powder, 1-3 parts of water reducer, 20-40 parts of silica fume, 180-220 parts of coarse aggregate, 60-80 parts of fine aggregate and 40-60 parts of water.
[0007] By adopting the above technical scheme, by calcining and modifying the fine powder of coal gangue, not only the effective utilization of resources is achieved, but also the dependence on natural sand and stone resources is reduced, which is conducive to environmental protection and sustainable development. High-temperature calcination can remove the carbon component in coal gangue and the hydroxyl contained in kaolinite, and the Si-O structure Al-O tetrahedral structure changes, which greatly improves the activation degree of coal gangue. Applying it in cement mortar can not only improve the compressive strength of concrete, but also enhance the durability of concrete. And through high-temperature calcination, useless coal and impurities in coal gangue are decomposed and volatilized, thereby reducing the impurity content, purifying coal gangue, and improving its purity. The silicate cement is combined with the calcined and modified fine powder of coal gangue, and is more closely combined with the cement hydration product, reducing the formation of cracks and voids inside the mortar, thereby improving the density and strength of the mortar, and can also play a role in improving the durability indicators such as the impermeability and freeze-thaw resistance of the mortar.
[0008] Optionally, the particle size of the coal gangue fine powder is 1-500 μm.
[0009] By adopting the above technical solution, fine coal gangue powder with a particle size within this range can be well filled in the gaps between cement particles and aggregate particles, forming a more compact stacking state. This helps to improve the density and strength of the mortar and reduce internal defects. Since smaller particles of coal gangue have a larger specific surface area, it can more easily promote the change of Si-O and Al-O structures, increase its active sites and reactivity, and help improve the activity of coal gangue.
[0010] Optionally, the preparation method of the calcined modified coal gangue fine powder is: A1. Mix the fine powder of coal gangue with water to form a slurry, then add sodium silicate, butyl xanthate and polyacrylamide into the slurry, stir at a speed of 300-500r / min for 5-15min, let it stand for stratification, remove the upper layer of liquid, and separate the fine powder of coal gangue; A2. Wash and dry the gangue fine powder, add 5-10% of the mass of the catalyst to the gangue fine powder, stir and mix evenly, transfer to a calcining furnace, and calcine at 700-800°C for 1-2h. After calcination, wash and dry to obtain calcined modified gangue fine powder.
[0011] By adopting the above technical scheme, in step A1, by mixing the fine powder of coal gangue with water to form a slurry, and adding sodium silicate, butyl xanthate and polyacrylamide after stirring and standing for stratification, some soluble impurities and impurities with good flotation properties in the fine powder of coal gangue can be preliminarily removed, wherein sodium silicate is used as a regulator, butyl xanthate is used as a collector, and polyacrylamide plays a role in enhancing the flotation effect. In step A2, 5-10% by mass of catalyst is added to the fine powder of coal gangue, and calcined at a temperature of 700-800°C. The addition of the catalyst can significantly reduce the activation energy during the calcination process, accelerate the phase change and reconstruction of the minerals in the coal gangue, and make it easier to transform or remove impurities. At the same time, the selection of the calcination temperature can ensure that the mineral components in the coal gangue undergo the required chemical reaction without causing excessive sintering or destroying its structure. The calcined and modified coal gangue fine powder has removed some impurities and improved its physical and chemical properties. Therefore, when added to concrete, it can significantly improve the strength and durability of concrete. The modified coal gangue fine powder can better combine with the cement matrix to form a denser microstructure.
[0012] Optionally, the addition amount of the sodium silicate is 0.5-2.5% of the mass of the coal gangue fine powder, the addition amount of the butyl xanthate is 0.1-1% of the mass of the coal gangue fine powder, and the addition amount of the polyacrylamide is 0.1-0.5% of the mass of the coal gangue fine powder.
[0013] Optionally, nitrogen is continuously introduced into the slurry during stirring in step A1.
[0014] The adoption of the above technical solution helps to improve the flotation separation effect.
[0015] Optionally, in step A2, the catalyst is one of iron oxide or copper oxide.
[0016] By adopting the above technical solution, at high temperature, the above catalyst can promote the phase change of the mineral components in the coal gangue, transforming it into a more stable and favorable mineral phase. These newly generated mineral phases may have better physical and chemical properties. Copper oxide is also an efficient catalyst that can promote various chemical reactions in the coal gangue during the calcination process. These reactions help remove impurities and improve the physical and chemical properties of the coal gangue.
[0017] Optionally, the water reducing agent is polymethacrylic acid, the coarse aggregate is blast furnace slag with a particle size of 5-25 mm, and the fine aggregate is machine-made sand with a particle size of 0.1-1 mm.
[0018] By adopting the above technical solution, polymethacrylic acid as a water reducer can significantly reduce the water-cement ratio of concrete, increase the fluidity of concrete, and help improve the construction performance of concrete. Blast furnace slag has high hardness and wear resistance. As a coarse aggregate, it can significantly improve the compressive strength and wear resistance of concrete. Artificial sand can fill the tiny gaps in concrete and increase the density and uniformity of concrete. Compared with natural sand, the particle shape and particle size distribution of artificial sand are more controllable, which helps to improve the working performance and strength of concrete. Choosing blast furnace slag and artificial sand as aggregate can not only effectively utilize industrial waste and renewable resources and reduce the consumption of natural resources, but also conform to the concept of green building and sustainable development.
[0019] In a second aspect, the present application provides a method for preparing high-strength mortar using fine powder of coal gangue, using the following technical solution: A method for preparing high-strength mortar using fine coal gangue powder comprises the following steps: S1. Add silicate cement, calcined modified coal gangue fine powder and silica fume into a mixing barrel, and use a stirrer to dry mix to ensure that various dry powder materials are evenly mixed to form a uniform dry mix; S2. Add water and water reducing agent into the mixing barrel, and stir at a speed of 50-80r / min until a uniform mortar-like mixture is formed; S3. Add coarse aggregate and fine aggregate into the mixing bucket and continue to stir and mix to form a uniform high-strength mortar.
[0020] By adopting the above technical solution, a uniform mortar-like mixture can be quickly formed through dry mixing and stirring. This method facilitates construction operations and improves construction efficiency.
[0021] In summary, this application has the following beneficial effects: 1. Since this application achieves effective resource reuse and reduces dependence on natural sand and gravel resources by high-temperature calcination modification of coal gangue fine powder, it is conducive to environmental protection and sustainable development. During the high-temperature calcination process, the mineral components in the coal gangue will undergo phase changes to form new mineral phases. These new phases often have higher activity and reactivity, can better combine with the hydration products in cement, form a tighter microstructure, and significantly improve the compressive strength and durability of concrete.
[0022] 2. In the present application, the above-mentioned technical scheme is preferably adopted. The soluble impurities and easily floated impurities in the coal gangue fine powder are effectively removed by adding flotation aids such as sodium silicate, butyl xanthate and polyacrylamide, thereby significantly improving the purity of the coal gangue fine powder. In the calcination modification stage, the catalyst is added for calcination, which not only accelerates the phase change and reconstruction process of the minerals in the coal gangue, but also promotes the further transformation and removal of impurities.
[0023] 3. The method of the present application realizes the effective utilization of coal gangue, reduces the dependence on natural sand and stone resources, and conforms to the concept of environmental protection and sustainable development. The high-strength mortar prepared by the method has excellent compressive strength, impermeability, freeze-thaw resistance and other properties, and can meet the needs of various construction projects. At the same time, the method also has the advantage of low cost, which helps to promote the green development and energy conservation and emission reduction of the construction industry. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments.
[0025] Preparation example of calcined modified coal gangue fine powder Preparation Example 1 A method for preparing calcined modified coal gangue fine powder: A1. Grind the gangue fine powder by a ball mill and screen it by a vibrating screen, select 10 kg of gangue fine powder with a particle size distribution of 1-500 μm, mix the gangue fine powder with 15 kg of water to form a slurry, then add 150 g of sodium silicate, 60 g of butyl xanthate and 30 g of polyacrylamide to the slurry, stir it at a speed of 400 r / min for 10 min, let it stand for stratification, remove the upper layer of liquid, and separate the gangue fine powder by filter press; A2. Wash and dry the gangue fine powder, add 800g of iron oxide, stir and mix evenly, transfer to a calcining furnace, and calcine at 750°C for 2h. After calcination, wash and dry to obtain calcined modified gangue fine powder.
[0026] Preparation Example 2 A method for preparing calcined modified coal gangue fine powder: A1. Grind the gangue fine powder by a ball mill and screen it by a vibrating screen, select 10 kg of gangue fine powder with a particle size distribution of 1-500 μm, mix the gangue fine powder with 15 kg of water to form a slurry, then add 150 g of sodium silicate, 60 g of butyl xanthate and 30 g of polyacrylamide to the slurry, stir it at a speed of 400 r / min for 10 min, and continuously introduce nitrogen into the slurry while stirring. After completion, let it stand for stratification, remove the upper liquid, and separate the gangue fine powder by filter press; A2. Wash and dry the gangue fine powder, add 800g of iron oxide, stir and mix evenly, transfer to a calcining furnace, and calcine at 750°C for 2h. After calcination, wash and dry to obtain calcined modified gangue fine powder.
[0027] Preparation Example 3 A method for preparing calcined modified coal gangue fine powder: The difference from Preparation Example 2 is that 50g of sodium silicate, 10g of butyl xanthate and 10g of polyacrylamide are added to the slurry.
[0028] Preparation Example 4 A method for preparing calcined modified coal gangue fine powder: The difference from Preparation Example 2 is that 250 g of sodium silicate, 100 g of butyl xanthate and 50 g of polyacrylamide are added to the slurry.
[0029] Preparation Example 5 A method for preparing calcined modified coal gangue fine powder: the difference from Preparation Example 2 is that no catalyst is added.
[0030] Preparation Example 6 A method for preparing calcined modified coal gangue fine powder: The difference from Preparation Example 2 is that step A1 is not performed.
[0031] Preparation Example 7 A method for preparing calcined modified coal gangue fine powder: The difference from Preparation Example 2 is that the particle size distribution of the coal gangue fine powder is 500-1000 μm. Example
[0032] Example 1 A method for preparing high-strength mortar using fine powder of coal gangue: S1. Add 6kg of Type I Portland cement, 5kg of calcined modified coal gangue fine powder, and 2kg of secondary silica fume into a mixing bucket, and use a stirrer to dry mix to ensure that all dry powder materials are evenly mixed to form a uniform dry mix; S2. Add 4 kg of water to a mixing barrel and simultaneously add 100 g of polymethacrylic acid having a molecular weight of 89.08924, and stir at a speed of 60 r / min until a uniform mortar-like mixture is formed; S3. Add 18 kg of blast furnace slag with a particle size of 5-25 mm and 6 kg of machine-made sand with a particle size of 0.1-1 mm into the mixing bucket, and continue to stir and mix to form a uniform high-strength mortar.
[0033] Among them, the calcined modified coal gangue fine powder is prepared by Preparation Example 2, Type I silicate cement is purchased from Jinan Qiansheng Chemical Co., Ltd., polymethacrylic acid is purchased from Xuzhou Yihuiyang New Materials Co., Ltd., and Al2O3 in blast furnace slag is greater than 20%, and CaO is greater than 50%.
[0034] Example 2 A method for preparing high-strength mortar using fine powder of coal gangue: S1. Add 10kg of type I silicate cement, 8kg of calcined modified coal gangue fine powder, and 4kg of secondary silica fume into a mixing bucket, and use a stirrer to dry mix to ensure that all dry powder materials are evenly mixed to form a uniform dry mix; S2. Add 6 kg of water to a mixing barrel and simultaneously add 300 g of polymethacrylic acid having a molecular weight of 89.08924, and stir at a speed of 60 r / min until a uniform mortar-like mixture is formed; S3. Add 22 kg of blast furnace slag with a particle size of 5-25 mm and 8 kg of machine-made sand with a particle size of 0.1-1 mm into a mixing bucket, and continue to stir and mix to form a uniform high-strength mortar.
[0035] Among them, the calcined modified coal gangue fine powder is prepared by Preparation Example 2, Type I silicate cement is purchased from Jinan Qiansheng Chemical Co., Ltd., polymethacrylic acid is purchased from Xuzhou Yihuiyang New Materials Co., Ltd., and Al2O3 in blast furnace slag is greater than 20%, and CaO is greater than 50%.
[0036] Example 3 A method for preparing high-strength mortar using fine powder of coal gangue: S1. Add 7kg of type I silicate cement, 7kg of calcined modified coal gangue fine powder, and 2.5kg of secondary silica fume into a mixing bucket, and use a stirrer to dry mix to ensure that all dry powder materials are evenly mixed to form a uniform dry mix; S2. Add 5 kg of water into a mixing barrel and simultaneously add 180 g of polymethacrylic acid having a molecular weight of 89.08924, and stir at a speed of 60 r / min until a uniform mortar-like mixture is formed; S3. Add 20 kg of blast furnace slag with a particle size of 5-25 mm and 7.5 kg of machine-made sand with a particle size of 0.1-1 mm into a mixing bucket, and continue to stir and mix to form a uniform high-strength mortar.
[0037] Among them, the calcined modified coal gangue fine powder is prepared by Preparation Example 2, Type I silicate cement is purchased from Jinan Qiansheng Chemical Co., Ltd., polymethacrylic acid is purchased from Xuzhou Yihuiyang New Materials Co., Ltd., and Al2O3 in blast furnace slag is greater than 20%, and CaO is greater than 50%.
[0038] Example 4 A method for preparing high-strength mortar using fine coal gangue powder: The difference from Example 3 is that the calcined modified coal gangue fine powder is prepared by Preparation Example 1.
[0039] Example 5 A method for preparing high-strength mortar using fine coal gangue powder: The difference from Example 3 is that the calcined modified coal gangue fine powder is prepared by Preparation Example 3.
[0040] Example 6 A method for preparing high-strength mortar using fine coal gangue powder: The difference from Example 3 is that the calcined modified coal gangue fine powder is prepared by Preparation Example 4.
[0041] Example 7 A method for preparing high-strength mortar using fine coal gangue powder: The difference from Example 3 is that the calcined modified coal gangue fine powder is prepared by Preparation Example 5.
[0042] Example 8 A method for preparing high-strength mortar using fine coal gangue powder: The difference from Example 3 is that the water reducer is calcium lignin sulfonate with a molecular weight of 528.61, purchased from Jinan Huisheng Chemical Co., Ltd., the coarse aggregate is crushed stone with a particle size of 5-25 mm, and the fine aggregate is river sand with a particle size of 0.1-1 mm.
[0043] Comparative Example Comparative Example 1 A method for preparing high-strength mortar using fine coal gangue powder: The difference from Example 3 is that in step S1, 7kg of type I silicate cement, 7kg of fine coal gangue powder with a particle size of 1-500μm, and 2.5kg of secondary silica fume are added to a mixing barrel, and dry mixing is performed using a stirrer to ensure that various dry powder materials are evenly mixed to form a uniform dry mix.
[0044] Comparative Example 2 A method for preparing high-strength mortar using fine coal gangue powder: The difference from Example 3 is that the calcined modified coal gangue fine powder is prepared by Preparation Example 6.
[0045] Comparative Example 3 A method for preparing high-strength mortar using fine coal gangue powder: The difference from Example 3 is that the calcined modified coal gangue fine powder is prepared by Preparation Example 7.
[0046] Performance testing Detection Methods The compressive strength and flexural strength were tested in accordance with GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete". The compressive strength specimen was a 100mm×100mm×100mm cube, and the flexural strength specimen was a 100mm×100mm×400mm prism. The chloride ion migration coefficient (RCM method) was used to test the durability of the concrete by testing its resistance to chloride ion penetration.
[0047] The test data are statistically sorted and summarized into the following table: Table 1 Strength / durability test data statistics Combining Example 3 and Comparative Example 1 with Table 1, it can be seen that since Comparative Example 1 uses coal gangue fine powder that has not been calcined and modified, it can be seen from the test results that whether it is tensile strength, flexural strength or durability, it is significantly lower than that of coal gangue fine powder concrete that has been calcined and modified. This shows that by calcining and modifying the coal gangue fine powder, the activation degree of the coal gangue is greatly improved. Applying it in cement mortar can not only improve the compressive strength of the concrete, but also enhance the durability of the concrete.
[0048] Combining Example 3 and Comparative Example 2 with Table 1, it can be seen that the difference between Example 3 and Comparative Example 2 is that the coal gangue fine powder in Comparative Example 2 is not subjected to flotation impurity removal treatment before calcination. It can be seen from the test results that flotation impurity removal can further reduce the impurities in the coal gangue fine powder and reduce the impact on concrete performance.
[0049] Combining Example 3 and Comparative Example 3 with Table 1, it can be seen that the difference between Example 3 and Comparative Example 3 is that no catalyst is added to the coal gangue fine powder during calcination in Comparative Example 2. It can be seen from the test results that the catalyst can react with the mineral components in the coal gangue at high temperature, accelerate the change and transformation of the mineral phase during calcination, thereby improving its activation degree, thereby improving the performance of the concrete.
[0050] It can be seen from Examples 1-3 and Table 1 that by changing the ratio of the components of the high-strength mortar made of fine coal gangue powder, the prepared concrete can achieve better strength and durability. Among them, the ratio in Example 3 is the best in this application.
[0051] It can be seen from Examples 3-7 and Table 1 that by adopting the method of first flotation to remove impurities and then high-temperature calcination, since some impurities are removed and their physical and chemical properties are improved, when added to concrete, the strength and durability of the concrete can be significantly improved, and the modified coal gangue fine powder can better combine with the cement matrix to form a denser microstructure. Continuously introducing nitrogen into the slurry during stirring helps to improve the flotation separation effect.
[0052] It can be seen from Example 3 and Example 8 and Table 1 that the water reducing agent is polymethacrylic acid, the coarse aggregate is blast furnace slag, and the fine aggregate is machine-made sand. Compared with conventional choices, the concrete can achieve better strength and durability.
[0053] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-strength mortar using fine powder of coal gangue, characterized in that: The components include 60-100 parts of silicate cement, 50-80 parts of calcined modified coal gangue fine powder, 1-3 parts of water reducer, 20-40 parts of silica fume, 180-220 parts of coarse aggregate, 60-80 parts of fine aggregate and 40-60 parts of water by weight.
2. The high-strength mortar using coal gangue fine powder according to claim 1, characterized in that: The particle size of the calcined modified coal gangue fine powder is 1-500 μm.
3. The high-strength mortar using fine coal gangue powder according to claim 1, characterized in that: The preparation method of the calcined modified coal gangue fine powder is: A1. Mix the fine powder of coal gangue with water to form a slurry, then add sodium silicate, butyl xanthate and polyacrylamide into the slurry, stir at a speed of 300-500r / min for 5-15min, let it stand for stratification, remove the upper layer of liquid, and separate the fine powder of coal gangue; A2. Wash and dry the gangue fine powder, add 5-10% of the mass of the catalyst to the gangue fine powder, stir and mix evenly, transfer to a calcining furnace, and calcine at 700-800°C for 1-2h. After calcination, wash and dry to obtain calcined modified gangue fine powder.
4. The high-strength mortar using coal gangue fine powder according to claim 3 is characterized in that: The addition amount of the sodium silicate is 0.5-2.5% of the mass of the coal gangue fine powder, the addition amount of the butyl xanthate is 0.1-1% of the mass of the coal gangue fine powder, and the addition amount of the polyacrylamide is 0.1-0.5% of the mass of the coal gangue fine powder.
5. The high-strength mortar using coal gangue fine powder according to claim 3 is characterized in that: In the step A1, nitrogen is continuously introduced into the slurry during stirring.
6. The high-strength mortar using fine coal gangue powder according to claim 3, characterized in that: In the step A2, the catalyst is selected from one of iron oxide and copper oxide.
7. The high-strength mortar using coal gangue fine powder according to claim 1, characterized in that: The water reducing agent is polymethacrylic acid, the coarse aggregate is blast furnace slag with a particle size of 5-25 mm, and the fine aggregate is machine-made sand with a particle size of 0.1-1 mm.
8. A method for preparing high-strength mortar using fine coal gangue powder according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Add silicate cement, calcined modified coal gangue fine powder and silica fume into a mixing barrel, and use a stirrer to dry mix to ensure that various dry powder materials are evenly mixed to form a uniform dry mix; S2. Add water and water reducing agent into the mixing barrel, and stir at a speed of 50-80r / min until a uniform mortar-like mixture is formed; S3. Add coarse aggregate and fine aggregate into the mixing bucket and continue to stir and mix to form a uniform high-strength mortar.